Promote the advance of the start of the growing season from combined effects of climate change and wildfire. (June 2021) - Rihan, Wu; Zhang, Hongyan; Zhao, Jianjun; Shan, Yu; Guo, Xiaoyi; Ying, Hong; Deng, Guorong; Li, Hui
Highlights: In the Mongolian Plateau, wildfires occurred frequently from 2001 to 2015. Advancing spring phenology more obvious in the Inner Mongolian than in Mongolia. Preseason temperature has the greatest impact on the spring phenology. In a typical fire area, the SOS in the fire zone shifted to earlier in the year. Abstract: The variation of land surface phenology (LSP) in natural ecosystems has received much attention at the regional and global scales. In this paper, we explore the relationship between variations in the start of the growing season (SOS) and their direct and indirect drivers for the Mongolian Plateau. Our results show that wildfire events mainly occurred in 2001, 2002, 2006, 2008, 2011, and 2016. The frequency of Mongolian wildfires is lower in the south and west, but higher in the east and north. The frequency of wildfires in Inner Mongolia (China) shows a spatial gradient, with a higher frequency in the northeast and a lower frequency in the southwest. Late SOS was most widely distributed in the southeast of Mongolia and the south of Inner Mongolia. The vegetation in the grassland or forest areas showed a comparatively early SOS, between the 110th and 130th day-of-year (DOY). The advancing trends of the SOS were mainly distributed around the northeast Mongolian Plateau, which is more obvious in Inner Mongolia (China) than in Mongolia. Under the control of precipitation (pre) and solar radiation, the preseason average temperature (Tmean ) in most areas of the study area is from 0 to 3 months. In the Mongolian Plateau, negative partial correlations between the SOS and preseason Tmean was mainly concentrated in the northern and northeastern parts of the study area, while positive correlations were mainly distributed in the central and southeastern parts. We also found that in addition to climate factors, wildfires have an impact on the SOS. After wildfires, the enhanced vegetation index (EVI), Tmean and SOS showed a significant difference in the greening period between the reference region and the burned area. Compared with the reference zone, the SOS in the fire zone shifted to being earlier. This study, therefore, provides a scientific basis and reference for understanding variations in the SOS in the study area and the response of the SOS to climate change and wildfires.